Effect of Diamond Polishing Pastes on the Polish Retention of Two Nanocomposites - م ت; م ن; م م; م م; م ت (Mashhad University of Medical Sciences, 2024)
Background: Finishing and polishing are important stages of composite restorations. Failure to polish will cause recurrent caries, plaque accumulation, and inflammation of the periodontium. This study evaluated the influence of diamond polish-pastes on the polish retention of the nanocomposites after pH-Cycling and tooth brushing.Materials and Methods: Forty cylindrical specimens including nanofilled composite (FiltekZ350) and nanohybrid composite (Aelite) were subjected to 4 polishing methods in 8 groups (n=5). A reference under Mylar strip (M), sequence of Sof-Lex discs(S), Sof-Lex discs and diamond polishing paste (TDV) (ST), and Sof-Lex discs and diamond polishing paste (Ultradent) (SU). After finishing and polishing, the Ra and Rz were determined by a profilometer for the first time. Specimens were subjected to a pH-cycling regimen and 10,000 brushing cycle. New readings of the Ra and Rz parameters were obtained. All sets of data were subjected to one-way ANOVA, Duncan multiple range test, and T-test.Results: In Z350 composite, the analysis of variance test showed a significant difference between Ra1 and Rz1 of the four investigated groups (P=0. 002, P=0. 003). After pH-cycling and brushing, Ra2 values showed significant differences among the four investigated groups (P=0. 009). The Rz2 values were not significantly different among the four groups (P=0. 353). In Aelite composite, the analysis of variance test showed a significant difference between Ra1 and Rz1 of the four investigated groups (P<0. 000, P=0. 004). After pH-cycling and brushing, Ra2 and Rz2 showed significant differences among the four investigated groups (P<0. 000, P<0. 000).Conclusion: Comparison of Rz and Ra in Z350 composite before and after pH-cycling and brushing indicated no significant difference. In other words, pH-cycling and brushing did not change the surface roughness. Aelite composite had higher Rz than Z350 composite before and after pH-cycling and brushing. Diamond polishing pastes had no effect on reducing surface roughness.